Genomic epidemiology of nosocomial carbapenemase-producing Citrobacter freundii in sewerage systems in the Helsinki metropolitan area, Finland - Heljanko, Viivi; Johansson, Venla; Räisänen, Kati; Anttila, Veli-Jukka; Lyytikäinen, Outi; Jalava, Jari; Weijo, Irma; Lehtinen, Jaana-Marija; Lehto, Kirsi-Maarit; Lipponen, Anssi; Oikarinen, Sami; Pitkänen, Tarja; et al. (Frontiers in Microbiology, 2023)
Multi-drug resistance is emerging in Citrobacter freundii, which is the third most common carbapenemase-producing (CP) Enterobacteriaceae in humans in Finland due to recent outbreaks. The objective of this study was to determine if wastewater surveillance (WWS) could detect CP C. freundii strains causing infections in humans. Selective culturing was used to isolate CP C. freundii from the hospital environment, hospital wastewater, and untreated municipal wastewater in Helsinki, Finland, between 2019 and 2022. Species were identified using MALDI-TOF, and presumptive CP C. freundii isolates were subjected to antimicrobial susceptibility testing and further characterized by whole genome sequencing. A genomic comparison was conducted to compare isolates collected from the hospital environment, untreated municipal wastewater, and a selection of isolates from human specimens from two hospitals in the same city. We also examined the persistence of CP C. freundii in the hospital environment and the impact of our attempts to eradicate it. Overall, 27 blaKPC − 2-carrying C. freundii were detected in the hospital environment (ST18; n = 23 and ST8; n = 4), while 13 blaKPC − 2-carrying C. freundii (ST8) and five blaVIM − 1-carrying (ST421) C. freundii were identified in untreated municipal wastewater. CP C. freundii was not identified in hospital wastewater. We found three clusters (cluster distance threshold ≤ 10 allelic difference) after comparing the recovered isolates and a selection of isolates from human specimens. The first cluster consisted of ST18 isolates from the hospital environment (n = 23) and human specimens (n = 4), the second consisted of ST8 isolates from the hospital environment (n = 4), untreated municipal wastewater (n = 6), and human specimens (n = 2), and the third consisted of ST421 isolates from the untreated municipal wastewater (n = 5). Our results support previous studies suggesting that the hospital environment could act as a source of transmission of CP C. freundii in clinical settings. Furthermore, the eradication of CP Enterobacteriaceae from the hospital environment is challenging. Our findings also showed that CP C. freundii is persistent throughout the sewerage system and demonstrate the potential of WWS for detecting CP C. freundii.